EMPOWERMENT PUBLIC TRANSPORTATION AS AN EDUCATIONAL SERVICES IN BORDER AREA - Anggraeni, Khurotin; Nasution, Abdul Haris; Kasimbara, Rachma Putri; Riwayati, Lutfia Okta (Erudio Journal of Educational Innovation, 2026)
The purpose on this study is to analysis the concept of empowerment of public transportation as an educational service in the border area. The focus of empowerment as an educational service is with the New Public Service paradigm. Public transportation empowered as an educational service in the border area is an interesting idea in the educational services needed. This study is used qualitative approach with constructivism paradigm to get the concept of empowerment publict transportation in educational services as an epistemology. The result of the study is the concept of empowerment focus on active participation to solve the problem itself and the development of local potential. The concept is used in the New Public Service paradigm to create opportunities for owners of public transportation to build community with a collaborative approach with parents and other owners of public transportation. The independent concept and prioritize on partnership between society and the owner of public transportation; however, the new public service paradigm limited listen society’s aspiration is not yet focused on providing facilities and collaboration between goverment with owner of public transportation, and society, such as subsidy programs and partnership with local governments to solve and provide educational services cheaply and safely. Whereas transportation for student is very important, not only as supporting infrastructure but also give many benefits in many aspects such as learning (student mobility, discipline, increasing student attendence, decresing drop out, supporting inclusion); Promotion (student engagement strategies); Protection, security, savety (anticipating juvenile delinquency, ensure safety and security); Maintain (maintaining rural transportation); and cost and welfare (affordable costs, and driver welfare)